The role of sulfur interactions in crystal architecture: experimental and quantum theoretical studies on hydrogen, halogen, and chalcogen bonds in trithiocyanuric acid–pyridine N-oxide co-crystals. Issue 2 (26th November 2020) - Wzgarda-Raj, Kinga; Palusiak, Marcin; Wojtulewski, Sławomir; Rybarczyk-Pirek, Agnieszka J.
Abstract : Hydrogen, halogen, chalcogen bonds and π interactions of the trithiocyanuric acid ring are responsible for crystal structure architecture and have been classified according to the QTAIM approach as closed-shell interactions. Abstract : Four new multicomponent crystals of trithiocyanuric acid with pyridine N -oxide derivatives have been synthesized. Trithiocyanuric acid affects the solid state molecular architecture of all the co-crystals. Various patterns of its intermolecular interactions responsible for crystal packing, including hydrogen, halogen and chalcogen bonds, have been recognized. The most characteristic pattern is formed via N–H⋯S hydrogen bonds, linking trithiocyanuric acid molecules into R22(8) synthons, which are further joined into linear, zig-zag double chain, cyclic, or infinite 2D supramolecular patterns. Using experimental X-ray and theoretical DFT geometric properties, the energy and electron density distribution of various trithiocyanuric acid interactions have been analyzed and characterized. This allowed the classification of the observed N–H⋯S hydrogen bonds as strong ones. There is an electron donating interaction of the N -oxide group with the trithiocyanuric acid ring center observed in two crystal structures. As shown in this article, the trithiocyanuric acid ring possesses electron deficiency and Lewis acid character. Therefore, it may be an acceptor of stabilizing contacts with electron donors, among others, the N -oxide group, which is known as a relatively strong Lewis base.